Prevention of Cervical Cancer among Mother in Yogyakarta, Indonesia - Nanik Setiyawati; Niken Meilani (Intelektual Pustaka Media Utama, 2018)
Cervical cancer was one of the global commitments in Sustainable Development Goals (SDGs). Cervical cancer represents 7.5% of all deaths caused by cancer in women. The method to screening cervical cancer is pap smear test and Visual Inspection of Acetic Acid (VIA) test. Indonesia is the second country in the world has the most cervical cancer cases. This study aims to determine the behavior of cervical cancer prevention on housewives. This is kuantitatif research with cross sectional design. The subjects of this study were housewives in the Kota Yogyakarta and Sleman regency amounting to 350 people. The analysis used is univariate, bivariate and multivariate analysis. The results showed that there were 45.1% of mothers' have did the implementation of VIA. There is a relationship of education (p = 0.024), level of knowledge (p = 0.036), and maternal attitudes with cervical cancer prevention behavior. There were no correlation between age (p = 0), parity (p = 0.816), and family income (p = 0.174) with the mother's behavior in the implementation of theVIA’s test. Multivariate analysis showed maternal attitude (CI = 0.335-0.788) that affect the behavior of the VIA.